Effects of different conditioning programmes on the performance of high-velocity soccer-related tasks: Systematic review and meta-analysis of controlled trials - Garcia-Ramos, A.; Haff, G. G.; Feriche, B.; Jaric, S. (International Journal of Sports Science & Coaching, 2018)
Physical performance is a key factor in most of the actions that determine success in soccer competitions. The present meta-analysis aimed to determine whether, and to what extent different conditioning programmes implemented in addition to regular soccer training are able to enhance the performance of high-velocity soccer-related tasks. Study groups were categorised according to type of performance measurement: (A) vertical jump ability, (B) linear sprint performance, (C), change of direction with ball, (D) change of direction without ball, (E) repeated sprint ability, and (F) kicking performance. Subgroup analyses were done with reference to the type of conditioning programme applied: (A) resistance training, (B) plyometric, (C) sprint and/or change of direction, and (D) combined methods. The standardised mean differences (SMD) along with 95% confidence intervals (95% CI) were calculated using the Review Manager 5.3 software. The application of a conditioning programme was associated with a significant improvement in vertical jump ability (SMD=0.64 [95% CI: 0.50-0.77]), linear sprint (SMD =-0.79 [95% CI: -0.61 to -0.96]), change of direction with ball (SMD=-0.78 [95% CI: -0.42 to -1.15]), change of direction without ball (SMD =-0.83 [95% CI: -0.61 to -1.05]), repeated sprint ability (SMD =-0.51 [95% CI: -0.19 to -0.84]), and kicking performance (SMD =-0.78 [95% CI: 0.34-1.22]). No clear differences among the different conditioning programmes were observed. The implementation of a conditioning programme in addition to regular soccer training enhances the performance of high-velocity soccer-related tasks. ABSTRACT FROM AUTHOR